Sistem pemantauan jarak jauh pergerakan zat radioaktif pada aliran dalam pipa (telemonitoring system for radioactive substance movement at stream in pipe) - Perpustakaan UGM, i-lib ([Yogyakarta] : LPM-UGM Bulaksumur Blok F-1,Yk 55281 Telp (0274)901170-901173 fax(0274)5153911, 2006)
ABSTRACT This research is intended to create the sufficient system, which is used for the real time telemonitoring system for radioactive substance movement at stream in pipe by using VHF Transceiver. The data managements which are developed in this research are expected to be used in the radioactive substance movement at stream in pipe monitoring system with the high accuracy. Detectors, which are used in this research, are SSD (Single Surface Detector) and SD (Semiconductor Detector). ADC 12 bits is used to convert the analog data becomes the digital data. Maximum data deviation is 0.0025 volt. Unlinearity of sensor system can be corrected by using software with the high level equation polynomial. Microcontroller functioned as controller of data traffic and also arranges the component job in the remote station and the controller station. DTMF is used for the technique of data delivery digitally. Using multivariable analog communications system enable to build the remote station in various location with the communications of radio of FM-VHF and frequency 144 MHz. Maximum reach from this telemetry system is 30 km, by using antenna